Avaliação de diferentes sistemas adesivos utilizados para fixação de retentores de fibra - Santos, Fernando Alberto Félix dos (2006)
The aim of this in vitro study was to evaluate which characteristics an adhesive system should have to provide a higher glass fiber post retention, considering humidity and light curing difficulty into root canals. It was utilized thirty bovine roots teeth that received glass fiber posts fixation. It was tested an hydrophilic adhesive: Optibond Solo Plus (in two different situations: photopolimerizable and modified for dual activation) and an hidrofobic and self-cured system (Concise). An universal machine was used to tensile tests, applying a continuous charge until the retainers displacement. The results indicate that hydrophilic adhesive system is essential to obtain a satisfactory hybridization and a consequent retention of fiber posts, and the adhesive activation for self-cure polymerization is recommendable to get a higher performance. Scaning eletronic microscopic images showed details of dentin, after tests.(AU)